MUATAN ETIKA DALAM PENGAJARAN AKUNTANSI KEUANGAN DAN PRESTASI BELAJAR SISWA TERHADAP PERSEPSI ETIKA PROFESI SISWA - Puji Hastuti (BAJ: Behavioral Accounting Journal, 2018)
This is a quantitative research which is done to the twelfth class of Accounting competence program of Ten State Vocational High School Surabaya. This research aims at finding out the influence of ethical content in Finance Accounting Teaching and Student’s Learning Achievement to the Student’s Profession Ethical Perception of the twelfth class students of Accounting Competence Program Department of Surabaya Ten State Vocational High School.The sample is taken by using the proportional random sampling technique. The amount of sample is 89 out of 114 students of the twelfth class of Accounting competence program department of Surabaya Ten State Vocational High School students.The Research Instrument Test is done first before taking the data. It covers the validity test and the reliability one. The method of collecting data is documentation and questionnaire. Analysis Prerequisite Test which is done is normality test, multicolonirity test, and heterocedasticity test. The analysis done in this research is doubled linear regression one. The result of the research shows that there is positive and significant influence of ethical content in Finance Accounting Teaching to the student’s profession ethical perception. This is shown by t-count as many as 5.133 with the significant score of 0.000 under the determined significant score standard of 0.05. While student’s learning achievement does not influence significantly to the student’s profession ethical perception. This is shown by t-count as many as 0.765 with the significant score of 0.446 above the determined significant standard as many as 0.05. However, there is positive influence simultaneously of the ethical content in Finance Accounting Teaching and the student’s profession ethical perception.